Peran Multidimensional Kiai dalam Pembentukan Karakter Disiplin Santri di Pesantren - Aprilia Herawati; Fata Asyrofi Yahya (Progressive Journal of Educational Science, 2026)
Disciplinary character of students at Nurul Azhar Islamic Boarding School in Sampung, Ponorogo. The study is based on the importance of character formation amid increasing moral issues in education. A qualitative case study approach was used to understand the phenomenon in its natural context. Data were collected through interviews, observations, and documentation involving one kiai, one administrator, and one student, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that the kiai plays a central role through three main functions: as a caregiver, motivator, and surrogate parent. As a caregiver, the kiai builds discipline through consistent role modeling and structured habituation. As a motivator, the kiai provides moral and spiritual encouragement that fosters students’ internal awareness of discipline. As a surrogate parent, the kiai establishes close emotional relationships that strengthen value internalization. These roles operate in an integrated and continuous manner. The study concludes that discipline is formed not only through formal rules but also through exemplary behavior, emotional closeness, and sustained guidance.